TUMPANG TINDIH PENGUASAAN TANAH ATAS DASAR SURAT GIRIK (STUDI PUTUSAN PN BEKASI NOMOR 591/PDT.BTH/2020/PN BKS): Overlapping Land Tenure Based On Girik Declaration (Study Of Bekasi District Court Decision Number 591/Pdt.Bth/2020/Pn Bks) - Samuel Yanandre Butar Butar; Dyah Setyorini (Reformasi Hukum Trisakti, 2025)
This study examines overlapping land ownership based on girik documents as one of the sources of legal conflict in Indonesia. The issues to be discussed are Are the judge's considerations in Decision Number 591/PDT.BTH/2020/PN.BKS in accordance with the UUPA and what are the legal consequences of overlapping land ownership based on the girik documents. This research is normative legal research and is descriptive in nature using secondary data obtained through literature studies, the data is processed qualitatively and conclusions are drawn using deductive logic. The results and conclusions of this study are the judge's considerations in Decision Number 591/PDT.BTH/2020/PN.BKS are in accordance with the UUPA by considering that the civil case decision Number: 268/Pdt.G/2012/PN.Bks; Jo. Number 302/PK/Pdt/2015 has permanent legal force (inkracht van gewijsde) and rejecting the Plaintiff's application as the owner of the disputed land is in accordance with the UUPA, namely Article 26 paragraph 2 of the UUPA, and Article 21 of the UUPA needs to be added in the judge's considerations. However, the legal consequences of dual certificates are the lack of legal certainty for land rights owners over the certificates they own.